2021
DOI: 10.1515/tnsci-2020-0177
|View full text |Cite
|
Sign up to set email alerts
|

miR-485-5p alleviates Alzheimer’s disease progression by targeting PACS1

Abstract: Alzheimer’s disease (AD) is a common dementia and a heterogeneous disease. Previous research has validated that microRNAs (miRNAs) are pivotal regulators in the initiation and development of tremendous diseases including AD. MicroRNA-485-5p (miR-485-5p) was reported to be an important participant implicated in several neurological diseases, but its role in AD still needs to be further investigated. In this research, we explored the biological function of miR-485-5p in AD. RT-qPCR revealed that miR-485-5p expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…MiRNAs are reported to participate in various neurological diseases. 28,29 Accumulating findings have confirmed that miR-33-5p is associated with the pathogenesis and progression of neurological disorders. MiR-33-5p downregulation protects neuronal cells from oxygen-glucose deprivation (OGD)-mediated cell death.…”
Section: Discussionmentioning
confidence: 94%
“…MiRNAs are reported to participate in various neurological diseases. 28,29 Accumulating findings have confirmed that miR-33-5p is associated with the pathogenesis and progression of neurological disorders. MiR-33-5p downregulation protects neuronal cells from oxygen-glucose deprivation (OGD)-mediated cell death.…”
Section: Discussionmentioning
confidence: 94%
“…Both microarray and clustering analyses revealed that the majority of DECEmiRs were classified into clusters 1–2, suggesting that DECEmiRs in clusters 1–2 are significantly correlated with AD progression. Importantly, many DECEmiRs in clusters 1–2, including let-7f-5p and miR-485-5p, have been reported with neuroprotective and anti-inflammatory effects in various in vitro and in vivo models of AD, indicating the potential involvement of DECEmiRs in AD pathogenesis ( Han et al, 2018 ; He et al, 2021 ). Since miRNAs achieve their biological functions mainly through regulating the expression of their targets, the functional analysis of the predicted targets of DECEmiRs may unveil underlying mechanisms that modulate the progression of AD.…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of miR-485-5p facilitated learning and memory capabilities (according to MWM and CFC tests), promoted pericyte viability, and suppressed Aβ40-induced pericyte apoptosis in APP/PS1 transgenic mice. Mechanistically, miR-485-5p directly targeted PACS1, a hallmark of AD, in pericytes [ 70 ]. As miR-485-5p was downregulated in the prefrontal cortex of patients with late-onset AD [ 75 ], miR-485-3p was overexpressed in the brain tissues, CSF, and plasma of patients with AD [ 71 ].…”
Section: Role Of Mirnas In Learning Memory and Cognitive Disordersmentioning
confidence: 99%